2022
DOI: 10.3389/fneur.2022.804207
|View full text |Cite
|
Sign up to set email alerts
|

Convergent and Divergent Structural Connectivity of Brain White Matter Network Between Patients With Erectile Dysfunction and Premature Ejaculation: A Graph Theory Analysis Study

Abstract: BackgroundSexual dysfunction, namely, erectile dysfunction (ED) and premature ejaculation (PE), has been found to be associated with abnormal structural connectivity in the brain. Previous studies have mainly focused on a single disorder, however, convergent and divergent structural connectivity patterns of the brain network between ED and PE remain poorly understood.MethodsT1-weighted structural data and diffusion tensor imaging data of 28 patients with psychological ED, 28 patients with lifelong PE (LPE), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Previous studies have identified abnormal neurological representations at the local, regional and global levels in pED patients. However, the fragmentation of these studies, along with the lack of systematic analysis of data, pose challenges for researchers in terms of acquiring a comprehensive understanding of the brain abnormalities associated with pED [20]. The definitive diagnosis of this disease remains controversial, making commonly used clinical tests such as NPTR, intracavernosal injection (ICI) + CDDU, and audiovisual sexual stimulation (AVSS) in-appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified abnormal neurological representations at the local, regional and global levels in pED patients. However, the fragmentation of these studies, along with the lack of systematic analysis of data, pose challenges for researchers in terms of acquiring a comprehensive understanding of the brain abnormalities associated with pED [20]. The definitive diagnosis of this disease remains controversial, making commonly used clinical tests such as NPTR, intracavernosal injection (ICI) + CDDU, and audiovisual sexual stimulation (AVSS) in-appropriate.…”
Section: Discussionmentioning
confidence: 99%